Lanthanide contraction and chelating effect on a new family of lanthanide complexes with tetrakis(O-isopropyl)methyle-nediphosphonate: synthesis, structures and terahertz time-domain spectroscopy. Issue 66 (25th August 2017) - Ma, Yan; Yang, Yong-Sheng; Jiang, Yu-Han; Li, Yue-Xue; Liu, Min; Li, Zhong-Feng; Han, Hong-Liang; Yang, Yu-Ping; Xin, Xiu-Lan; Jin, Qiong-Hua
Abstract : Sixteen lanthanide–diphosphate complexes have been synthesized by the reaction of lanthanide chlorides and tetrakis( O -isopropyl)methylenediphosphonate ligand in the solvent of acetonitrile (with ethanol or DMF) at room temperature. Abstract : Sixteen lanthanide–diphosphate complexes [LnL2 (H2 O)4 Cl]Cl2 (Ln = La 3+ for1, Ln = Ce 3+ for2 ), [LnL2 (H2 O)4 ]Cl3 ·6H2 O (Ln = Nd 3+ for3, Ln = Sm 3+ for4, Ln = Eu 3+ for5, Ln = Gd 3+ for6, Ln = Tb 3+ for7, Ln = Dy 3+ for8, Ln = Er 3+ for9 ), [LaL2 (H2 O)4 Cl]Cl2 2 (10 ), [PrL2 (OH)2 (H2 O)Cl] [PrL2 (H2 O)4 Cl]Cl2 (11 ), [LaL2 (H2 O)5 Cl]Cl2 ·2H2 O (12 ), [YbL2 (H2 O)3 Cl]Cl2 ·H2 O (13 ), [NdL2 (H2 O)3 Cl]Cl2 ·3H2 O (14 ), [HoL2 (H2 O)Cl2 ]Cl·H2 O (15 ), [Sc2 L2 (H2 O)4 (OH)2 ]Cl4 ·4H2 O·2CH3 OH (16 ) (L = tetrakis( O -isopropyl)methylenediphosphonate) have been synthesized by the reaction of lanthanide chlorides and L ligand in the solvent of acetonitrile (with ethanol or DMF) at room temperature. The title complexes were characterized by IR, elemental analysis, single-crystal X-ray diffraction analysis, thermal analysis, 1 HNMR and 31 PNMR spectroscopy. Complexes1–15 are mononuclear complexes and complex16 is a binuclear cluster complex. Complex12 is the intermediate of complex1 . Complexes11–13 display a one-dimensional chain formed by hydrogen bonds and the structures of complexes14, 16 can be simplified as two-dimensional mesh 6 3 topology formed by hydrogen bonds. In those lanthanide complexes, the lanthanide ion with an atomic number smaller than Pr element tends to form a nine-coordinated structure and that with the atomic number larger than Pr element tends to form an eight or lower number-coordinated structure. Pr element has two kinds of coordination situations, with coordination numbers of nine or eight. The terahertz (THz) time-domain spectra of these complexes were also studied.